Analisis Getaran Pada Bus Trans Jateng Koridor 4 Menggunakan Sensor Akselerometer MPU6050 Dan Metode RULA - Wisnumurti, Muhammad Hanafi; Mukhtar, Agus; Burhanuddin, Aan (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
Public bus drivers are at risk of health issues due to mechanical vibrations and non-ergonomic working postures during long working hours. This study analyzed vibration levels and ergonomic risks of Trans Jateng Corridor 4 bus drivers using an experimental method with an MPU6050 accelerometer sensor at three points: brake/clutch pedal, steering wheel, and driver’s seat at various operational speeds. Ergonomic assessment was conducted using the Rapid Upper Limb Assessment (RULA) method with CATIA V5R20 software during two main work phases. Results showed the highest vibration level on the brake/clutch pedal (3.23 m/s²), still below the threshold limit of 5 m/s² for 6–8 hours of work as regulated by the Ministry of Manpower Decree No. 5/2018. The lowest vibrations were recorded on the steering wheel (0.79 m/s²) and driver’s seat (0.93 m/s²). A RULA score of 3 in both phases indicated a “low risk” category but required long-term preventive measures. Recommendations include the use of anti-vibration footwear, structured breaks every 90 minutes, and driver rotation with a maximum of 6 hours per shift to maintain optimal working conditions and prevent occupational health disorders.